The voyage on the Oddest Sea - Boyer, Crispin; Elkerton, Andy (Washington D.C : National Geographic, 2023)
Zeus the hamster and his team of Olympians travel to the aquatic realm of Poseidon, where they fight to regain the pufferfish's throne from the usurper Proteus--a mimic octopus and the newest addition to the pet shop.
Ages 8-12.
Keywords: Mythology, Greek -- Juvenile fiction; Fantasy fiction